2019
DOI: 10.1029/2018ja026013
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Ionospheric Potential Pattern by Ionospheric Hall Polarization

Abstract: The present study shows that the ionospheric Hall polarization can deform the high‐latitude ionospheric convection field, which is widely considered to be a manifestation of the convection field in the magnetosphere. We perform the Hall polarization field separation with a potential solver by changing the conductance distribution step by step from a uniform one to a more realistic one. We adopt dawn‐dusk and north‐south symmetric distributions of conductance and region 1 (R1) field‐aligned current (FAC). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Shue and Weimer (1994) had proposed that polarization electric fields around areas of enhanced conductivity are responsible for forming the Harang discontinuity; the effect is to block the divergence of Hall currents where there are gradients in the Hall conductivity. Further evidence of this concept has been provided by Nakamizo and Yoshikawa (2019), and our results are consistent with this hypothesis. Equations 7and 8are not accurate where there are conductivity gradients, so the derived conductivity values near midnight, from 22 to 2 MLT, should not be trusted.…”
Section: Discussionsupporting
confidence: 92%
“…Shue and Weimer (1994) had proposed that polarization electric fields around areas of enhanced conductivity are responsible for forming the Harang discontinuity; the effect is to block the divergence of Hall currents where there are gradients in the Hall conductivity. Further evidence of this concept has been provided by Nakamizo and Yoshikawa (2019), and our results are consistent with this hypothesis. Equations 7and 8are not accurate where there are conductivity gradients, so the derived conductivity values near midnight, from 22 to 2 MLT, should not be trusted.…”
Section: Discussionsupporting
confidence: 92%
“…Data used in the development of the fieldaligned current model are available through Edwards et al (2020). The electric potential model (Edwards, 2019) was developed with the Swarm cross-track ion drift data available at https://swarm-diss.eo.esa.int/#swarm/Advanced/Plasma_Data/ 2Hz_TII_Cross-track_Dataset (Burchill and Knudsen, 2020) and Dynamics Explorer 2 Vector Electric Field measurements at https://cdaweb.gsfc.nasa.gov/pub/data/de/de2/electric_fields_vefi/ (last access: 12 January 2021, Maynard et al, 1981 Frandsen et al, 1978;Coplan et al, 1978), and data from ACE are available at https://cdaweb.gsfc.nasa.gov/pub/data/ace/mag/level_2_cdaweb/ and https://cdaweb.gsfc.nasa.gov/pub/data/ace/swepam/level_2_ cdaweb/swe_h0 (last access: August 2019, Smith et al, 1998;McComas et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…According to their results, the pattern of the equivalent currents related to the high‐latitude convection showed a clockwise rotation for all the cases of the IMF By pattern under the negative value of the IMF Bz . Recently, Nakamizo and Yoshikawa (2019) clarified that the deformation of the high‐latitude convection pattern is established by the combined effects of the solar wind and ionospheric polarization due to the spatial inhomogeneity of ionospheric conductivities with the use of an electric potential solver (Nakamizo et al, 2012). In this study, it was newly shown that the SED plume can expand from the afternoon or evening sector to the prenoon sector and move toward the high‐latitude region from the throat region between the dawn and dusk convection cells due to the clockwise rotation of the high‐latitude convection pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the above discussion, it can be considered that the structure of the SED plume strongly depends on the high‐latitude convection pattern. According to Nakamizo and Yoshikawa (2019), since the spatial distribution of the high‐latitude convection depends on both the solar wind and ionospheric conductivities, the statistical feature of the SED plume will be established by a statistical analysis in future studies.…”
Section: Discussionmentioning
confidence: 99%